Pemodelan Sistem Pakar Pendeteksian Kerusakan Printer Berbasis Website Dengan Metode Forward Chaining : Studi Kasus : SDN Pela Mampang 03 Pagi - Juliana Zega; Rizal Rizal (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
An expert system is a collection of system engineering devices which have a structured way of thinking from one or more experts regarding certain scientific fields, both specific and complex, which are created based on an instructional element that identifies and also analyzes data at the level of irregular problems or analysis. mathematics regarding problems that cover certain aspects, but are related to the process of detecting printers and repairing them from the school which is carried out independently, then along with the development of website-based information technology which can make it easier to detect printer damage for users, then in detecting printer damage for users there are several factors that influence this, such as, not all staff at the school have knowledge in detecting printer damage and there is no system that supports detecting printer damage so it is difficult to find solutions for staff to repair, based on this problem as a solution, an expert system application design is needed. for detecting printer damage to users who support the website-based printer detection process using the forward chaining method, the concept of forward chaining with search or forward tracking techniques starting with existing information or combining rules to obtain a certain conclusion or goal as a result of the solution.